2021
DOI: 10.1186/s12903-021-01704-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dental caries and associated factors among secondary school children in rural highland Vietnam

Abstract: Background To determine the prevalence of dental caries in primary and permanent teeth and identify factors associated with dental caries among secondary school children in rural highland Vietnam. Methods This was a cross-sectional study that included 1985 secondary schoolchildren. Dental examination was performed at school using World Health Organization criteria. Data collection on demographic characteristics and knowledge, attitude, and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…Oral diseases, dominated by dental caries, are a global health concern because they affect more than half of the population [ 1 , 2 , 3 ]. Other oral diseases, such as oral lesions and manifestations, including signs and symptoms of oral or systemic diseases, can negatively affect children and adolescents and impact their quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral diseases, dominated by dental caries, are a global health concern because they affect more than half of the population [ 1 , 2 , 3 ]. Other oral diseases, such as oral lesions and manifestations, including signs and symptoms of oral or systemic diseases, can negatively affect children and adolescents and impact their quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of dental caries was 31.78% (75/236) in children aged 3 years, 42.81% (131/306) in children aged 4 years and 56.31% (223/396) in children aged 5 years. Some studies have suggested that age is an independent risk factor for dental caries in preschool children, as primary teeth continue to function before replacement, resulting in persistent and cumulative effects, therefore, the growth of the age associated with the risk and degree of preschool children's dental caries [12].Another study showed that the caries rate of primary teeth of children in the younger age group was higher than that of children in the older age group [13].Therefore, as a cross-sectional study, this study cannot con rm whether the occurrence of dental caries is related to age. As a chronic disease, childhood dental caries may have a cumulative effect in older children.…”
Section: Discussionmentioning
confidence: 99%
“…The potential explanations include the high prevalence of cariogenic bacteria in the primary dentition may have a spillover effect on the newly erupted teeth [ 11 , 12 ]. Another possible cause would be common risk factors that affect both dentitions, such as sociodemographic factors, oral hygiene maintenance and dietary habits that have not been modified from childhood to adolescence [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%